2015
DOI: 10.1007/s10113-015-0865-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between rural–urban migration flows and urban air quality in China

Abstract: In light of the rapid urbanization of the world's population over the past decades, there is a growing concern about the environmental impacts of urban population growth. Rural-urban migration is a particularly important component of the urbanization process in developing countries and is often considered to be detrimental to urban environmental conditions. However, few studies have explicitly examined the presumed negative impacts of inmigration on the natural environment of cities. The continuously increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…To account for the regional variation of air quality, many researchers have examined the influencing factors relevant to urban air quality. In these studies, factors as meteorological elements, land use and land cover change, urbanization, industrialization, energy structure, and transport patterns have been reported to have significant impact on urban air quality (Krummel et al, 1984;Shaw et al, 2010;Tai et al, 2010;Zhang and Fan, 2011;Guan et al, 2014;Lu and Han, 2014;Patton et al, 2014;Li et al, 2015;Lin and Wang, 2016;Qin and Liao, 2016;Sun et al, 2016;Zou et al, 2016;Hu et al, 2017;Yan et al, 2017). The previous studies, in general, have predominantly observed the characteristics of determinants within a single region or among different cities.…”
Section: Introductionmentioning
confidence: 99%
“…To account for the regional variation of air quality, many researchers have examined the influencing factors relevant to urban air quality. In these studies, factors as meteorological elements, land use and land cover change, urbanization, industrialization, energy structure, and transport patterns have been reported to have significant impact on urban air quality (Krummel et al, 1984;Shaw et al, 2010;Tai et al, 2010;Zhang and Fan, 2011;Guan et al, 2014;Lu and Han, 2014;Patton et al, 2014;Li et al, 2015;Lin and Wang, 2016;Qin and Liao, 2016;Sun et al, 2016;Zou et al, 2016;Hu et al, 2017;Yan et al, 2017). The previous studies, in general, have predominantly observed the characteristics of determinants within a single region or among different cities.…”
Section: Introductionmentioning
confidence: 99%
“…urban China (Qin and Liao, 2016). Since China's reform and opening up, a rapid urbanization process has been sustained (Cao and Liu, 2011).…”
mentioning
confidence: 99%
“…Additionally, this boost to the rural economy and subsequent employment opportunities for rural youth may lead to lower rural-urban migration, an issue that has been linked to socio-demographic and environmental problems (Qin & Liao 2016). Increased income and, consequently, increased demand by the rural populations, along with a more productive workforce would positively contribute to economic growth (Besley & Cord 2006;Ravallion 2004).…”
Section: Literature Reviewmentioning
confidence: 99%